2015
DOI: 10.2337/db14-1030
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal AAV2.COMP-Ang1 Prevents Neurovascular Degeneration in a Murine Model of Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is the leading cause of blindness in the working-age population in the U.S. The vision-threatening processes of neuroglial and vascular dysfunction in DR occur in concert, driven by hyperglycemia and propelled by a pathway of inflammation, ischemia, vasodegeneration, and breakdown of the blood retinal barrier. Currently, no therapies exist for normalizing the vasculature in DR. Here, we show that a single intravitreal dose of adeno-associated virus serotype 2 encoding a more stable, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 48 publications
7
56
2
Order By: Relevance
“…In late DR, AAV2.COMP-Ang1 enhanced the therapeutic benefit of intravitreally delivered endothelial colony-forming cells, a key vascular-derived progenitor population, by promoting their integration into the vasculature. 24 This puts forth the idea of gene therapy for DR and that AAV2.COMP-Ang1 single dose could be considered in the future as a targeted therapy to prevent neurovascular pathology, support vascular regeneration, and even stabilize vision in DR.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…In late DR, AAV2.COMP-Ang1 enhanced the therapeutic benefit of intravitreally delivered endothelial colony-forming cells, a key vascular-derived progenitor population, by promoting their integration into the vasculature. 24 This puts forth the idea of gene therapy for DR and that AAV2.COMP-Ang1 single dose could be considered in the future as a targeted therapy to prevent neurovascular pathology, support vascular regeneration, and even stabilize vision in DR.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Intriguingly, Ang2 overexpression in the retina or its intravitreal injection in rodent models enhances vascular impairment, suggesting that it plays a role in diabetic vasoregression by destabilizing pericytes, inducing similar damages to those observed in early diabetic retinopathy [87,88]. Conversely, intraocular injection of Ang1 suppressed retinal edema in diabetic mice [89]. This delivery method is also attractive because it reduces the generalized side effects seen with systemic administration.…”
Section: Diabetic Retinopathymentioning
confidence: 97%
“…High Ang1 levels might act synergistically with elevated VEGF in the diabetic retina to induce angiogenic changes [27]. It was recently demonstrated that adeno-associated virus serotype 2 encoding a more stable, soluble and potent form of Ang1 (AAV2.COMP-Ang1) can improve the structural and functional hallmarks of diabetic retinopathy in Ins2Akita mice [89].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…The advent of intraocular drug delivery of steroids and anti-vascular endothelial growth factor (VEGF) inhibitors over the past decade has established the principle of direct pharmacotherapy for diabetic retinopathy. Additional pathways, including plasma kallikrein signaling 38 , loss of neurotrophic support 39, 40 , and deficient angiopoietin 1 signaling 41 may be targets for future therapy. Direct ocular drug administration will continue to be a major route of diabetic retinopathy treatment with sustained delivery methods now in clinical testing 42 .…”
Section: Pathophysiology Of Diabetic Retinopathymentioning
confidence: 99%